Resistance and resilience of social–ecological systems to recurrent typhoon disturbance on a subtropical island: Taiwan. Issue 1 (5th January 2018) - Chang, Chung‐Te; Vadeboncoeur, Matthew A.; Lin, Teng‐Chiu
Abstract: Tropical cyclones (TCs) have major effects on ecological and social systems. However, studies integrating the effects of TCs on both social and ecological systems are rare, especially in the northwest Pacific, where the frequency of TCs (locally named typhoons) is the highest in the world. We synthesized studies of effects of recurrent typhoons on social and ecological systems in Taiwan over the last several decades. Many responses to TCs are comparable between social and ecological systems. High forest ecosystem resistance, evident from tree mortality below 2% even following multiple strong typhoons, is comparable with resistance of social systems, including the only 4% destruction of river embankments following a typhoon that brought nearly 3000 mm rainfall in three days. High resilience as reflected by quick returns of leaf area index, mostly in one year, and streamwater chemistry, one to several weeks to pre‐typhoon levels of ecosystems, are comparable to quick repair of the power grid within one to several days and returns of vegetable price within several weeks to pre‐typhoon levels of the social systems. Landslides associated with intense typhoons have buried mountain villages and transported large quantities of woody debris to the coast, affecting the coastal plains and reefs, illustrating a ridge‐to‐reef link between ecological and societal systems. Metrics of both social and ecological function showed large fluctuations in response to typhoons but quickly returned to pre‐disturbance levels, except when multiple intense typhoons occurred within a single season. Our synthesis illustrates that the social–ecological systems in Taiwan are highly dynamic and responsive to frequent typhoon disturbance, with extraordinarily high resistance and resilience. For ecosystems, the efficient responsiveness results from the selective force of TCs on ecosystem structure and processes. For social systems, it is the result of the effects of TCs on planning and decision making by individuals (e.g., farmers), management sectors, and ultimately the government. In regions with frequent TCs, the social–ecological systems are inevitably highly dynamic and rapid responses are fundamental to system resistance and resilience which in turn is key to maintaining structure and function of the social–ecological systems.